Santri’s Humility in the Salafiyyah Islamic Boarding School - Rahmatullah, Azam Syukur; Azhar, Muhammad; Fatwa, Ahmad Fajruddin (Dinamika Ilmu: Jurnal Pendidikan, 2021)
This research belongs to qualitative research, which explored the tawadhu' (humility) in the Lirboyo Islamic Boarding School, Kediri. Tawadhu' in Islamic boarding school is traditional, rooted, and has become a positive character. Thus, it deserves to be explored and later can be used as a "role model" for other educational institutions to implement, develop and produce individuals with this character. The method used was field research with an ethnomethodological approach, a cluster of qualitative research that focused on reality with practical interpretation. Research results showed that the notion of tawadhu', according to the kyai's perspective at the Lirboyo Islamic Boarding School, Kediri, was an effort to transfer values and morality to the santri. Thus, they would possess polite behavior, obey goodness and virtue, will be kind to others. Second, tawadhu' had several foundational factors at the Salafiyyah Lirboyo Islamic Boarding School, East Java, including (a) spiritual foundations, (b) struggling mental foundations, (c) prosocial foundations. The objectives of tawadhu' for the santri at the Salafiyyah Lirboyo Islamic Boarding School, East Java, were: (a) growing value education in the students, (b) Preventing self-deception and misdirection to others, (c) building and instilling muhsin's personality to the students. Creating the teachings of tawadhu' at the Lirboyo Islamic Boarding School, Kediri was influenced by several factors: (a) the kyai's charisma, (b) the continuous book learning, and kaffah internalization to students. Many teachings have educated students in the books studied to be humble, obedient, and glorify others.